Transformation of 2D Animated Botany Learning to Recognise Types of Roots and Leaves in Plants - Pakpahan, Antonius Christian (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
Digital transformation has opened opportunities for innovation in the world of education, including in the field of botany. This study aims to develop and test the effectiveness of a 2D animation-based learning media to help students learn about the types of roots and leaves in plants. This material is often considered abstract and boring when delivered only through conventional methods such as textbooks or static images. The research method used is Research and Development (R&D) with the Multimedia Development Life Cycle (MDLC) model, which consists of six stages: Concept, Design, Material Collecting, Assembly, Testing, and Distribution. In the concept stage, an analysis of student needs and learning difficulties was conducted. The design stage involved the creation of storyboards and scripts. The assembly stage was the process of producing 2D animations using Adobe Animate software. The final product was then implemented among elementary school students and evaluated. The results of validation from material and media experts stated that the 2D animation media was highly feasible. Testing on students showed a significant increase in post-test scores compared to pre-test scores, indicating that this media is effective in improving students' understanding and recognition of root and leaf types. The conclusion of this research is that 2D animation is a transformative medium that is not only engaging and interactive but has also been proven to facilitate a better understanding of plant morphology concepts. It is recommended that educators utilize similar media in biology instruction.